USM CONTINUES TO SUPPORT WHO ‘NO TOBACCO’ INITIATIVE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 31 May 2016 – The World Health Organisation (WHO) has designated 31 May each year as the ‘World No Tobacco Day’. The theme which has been decided by WHO this year is ‘Get Ready for Plain Packaging’.